(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The data on the health status of a policyholder represent a significant circumstance for risk assessment and concluding a life insurance contract, and are also legally relevant circumstances for exercising the rights from that contract. The author starts from a theoretical analysis of the perception of data on the health status of policyholders as personal data, comparing the right to confidentiality of such data with the duty to report them (before concluding a life insurance contract) in terms of reporting all circumstances relevant to the insurance risk assessment. In order to properly fulfil the obligation of pre-contractual nature, the paper analyses the legal norms governing this issue and also provides a comparative overview of the Croatian and German insurance legislation with special emphasis on the scope of health data that the insurer is authorised to require, the clarity of legal standards and legal insurance norms contained in the insurance questionnaires and the life insurance offer. Presenting the importance of COVID-19 infection and possible chronic consequences for human health, the author indicates the extent to which COVID-19 infection (mild or severe form of disease, possible need for hospital treatment) will have an impact on the design of new insurance questionnaires and the relevance of genetic testing results in the context of concluding future life insurance contracts.